Testing the Fabric: Prescribing Female Dress in Australian Early Living-Wage Cases. Issue 37 (September 2016) - Dick, Caroline
Abstract : In the first two decades after the creation of the Federation of Australia in 1901 Justice Henry Bournes Higgins and his fellow Arbitration Court and Board of Trade judges used the contestation over dress in female living-wage cases to reinforce male hegemony via discrimination towards female workers and to set prescriptive sumptuary standards of dress for them. This article illustrates how these judicial officers embraced the same type of objectives embodied in earlier sumptuary codes when they adopted a new legal and social role as arbiters of taste and normative 'appropriateness' in female dress. As men of authority and power, they positioned themselves to decide gendered questions such as what represented a reasonable amount for female factory workers to spend on their clothes.